2018
DOI: 10.1002/em.22173
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage‐induced apoptosis and mitogen‐activated protein kinase pathway contribute to the toxicity of dronedarone in hepatic cells

Abstract: Dronedarone, an antiarrhythmic drug, has been marketed as an alternative to amiodarone. The use of dronedarone has been associated with severe liver injury; however, the mechanisms remain unclear. In this study, the possible mechanisms of dronedarone induced liver toxicity were characterized in HepG2 cells. Dronedarone decreased cells viability and induced apoptosis and DNA damage in a concentration- and time-dependent manner. Pretreatment of the HepG2 cells with apoptosis inhibitors (caspase-3, -8, and -9) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Our previous study investigated dronedarone-induced toxicity after 6 h treatment and demonstrated that there was significant cytotoxicity when cells were treated with drone-darone at 10 μM for 6 h (Chen et al 2018). It has been reported that dronedarone can be detected within 24 h incubation in metabolically competent human primary hepatocytes (Klieber et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study investigated dronedarone-induced toxicity after 6 h treatment and demonstrated that there was significant cytotoxicity when cells were treated with drone-darone at 10 μM for 6 h (Chen et al 2018). It has been reported that dronedarone can be detected within 24 h incubation in metabolically competent human primary hepatocytes (Klieber et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Significant cytotoxicity was observed in both cell lines, but HepG2 cells displayed a higher sensitivity to dronedarone than the metabolically competent HepaRG cells (Chen et al 2018). These results stimulated the current investigation to determine which drug-metabolizing enzymes are most important in the toxicity or detoxification of dronedarone, i.e., whether they enhance or reduce its toxicity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations